Innovation Outposts in Entrepreneurial Ecosystems: How to Make Them More Successful. (May 2021) - Decreton, Benoit; Monteiro, Felipe; Frangos, Jean-Marc; Friedman, Lisa
Startups in entrepreneurial ecosystems such as Silicon Valley constantly generate potentially disruptive technologies and business models. Consequently, multinational companies are finding it essential to be connected to the ecosystems where these opportunities are emerging, and many have opened "innovation outposts" in these locations. However, not many outposts succeed in effectively connecting their companies with these ecosystems. This article details why outposts often fail to become "effective brokers" and what companies should do for their outposts to deliver their full potential.